The association of metabolic syndrome risk factors with serum high-molecular weight adiponectin and urinary metabolites among the orang asli in Malaysia - Ashari, Lydiatul Shima (2016)
Orang Asli (OA) are the indigenous people of Peninsular Malaysia. Overall, there are 18 subtribes of OA which are categorised under three main tribes namely Senoi, Proto Malay, and the Negrito. The association of metabolic syndrome (MetS) risk factors with serum high-molecular weight (HMW) adiponectin and urinary metabolites among OA tribes are scantly reported. The purpose of this study was to determine the association of MetS risk factors with serum HMW adiponectin and urinary metabolites among the OA population in Peninsular Malaysia. This crosssectional study was conducted according to the geographical locations of OA subtribes namely Che Wong, Kensiu, Semai, Orang Kanaq, Lanoh, and Bateq by simple random sampling method. The purposive and snow-ball sampling methods were used to select 185 respondents aged 18 years and above. The respondents were measured for their weight, height, waist circumference (WC), and blood pressure. Overnight fasting venous blood samples were analysed for lipid profiles, plasma glucose, and HMW adiponectin while urine samples were analysed for metabolite profiles using metabolomics approach. The overall prevalence of MetS was 29.7% (55/185). MetS prevalence was significantly higher in female (36.2%) compared to male (21.3%) respondents. MetS was also higher among the suburban Orang Kanaq (81.8%) and Kensiu (36.4%) subtribes and lower among rural Semai (23.8%) andBateq (8.0%) subtribes (p<0.001). Females had significantly higher rates of high WC (45.7% vs. 2.5%, p<0.001) and low HDL-C (69.5% vs. 31.3%, p<0.001) compared to males. Area under ROC curve (AUROC) analysis showed that 22 metabolites were determined as potential urinary metabolite biomarkers of MetS with area under the curve (AUC) of at least 0.7. Multiple linear regression models revealed that HMW adiponectin were negatively associated with WC (β=-0.07; p=0.001) and sex (β=-1.53; p<0.001) but positively associated with age (β=0.05; p=0.004). Besides, urinary 3-ethyl-3-methyl-tridecanoic acid (C16H32O2) level was positively associated with systolic blood pressure (β=0.06; p=0.031). This urinary metabolite was not associated with HMW adiponectin in multiple linear regression models but it was correlated with HMW adiponectin in Spearman correlation analysis. This study could provide clues and additional insight into the pathogenic mechanism of MetS among OA population.